TELAAH KEJAHATAN KEMANUSIAAN TERHADAP ETNIS ROHINGYA BERDASARKAN HUKUM INTERNASIONAL - Inggrit Fernandes; M. Rizqi Azmi (Fakultas Hukum Universitas Islam Indragiri, 2017)
International law is a law whose enforcement depends on the good faith of the countries thatare members of the world community. It can only be imposed if the state does not have thepower of lobbying in international relations. The proof of many countries that violate the lawof intrenasional but has a strong ally then he is detached from the bondage of internationallaw itself. International humanitarian law has been in existence since the formation of theUnited Nations but its implementation has been dulled by the high-level lobby of the UNSecurity Council. Crimes against ethnic Rohingya should be prosecuted in the InternationalCriminal Court (ICC) because there are already elements of violations in the Rome Statute1998.